Effect of Commercial Cationic Starch on Paper Properties Made from Recycled Pulp (Malaysian Journal of Bioengineering and Technology, 2024)
The production of packaging paper is growing steadily annually globally. Packaging paper such as liner paper and medium paper are mainly made from recycled pulp. The strength of pulp deteriorated over the cycle of recycling. To ensure the packaging paper strength produced from recycled paper is up to par, the additive is mandatory. Starch is one of the common and economical additives used in papermaking. In this research, the performance of commercial cationic starch as an additive in packaging papermaking is evaluated.  4 different percentages of starch, including 2%, 4%, 6%, and 8%, were studied. Five replicates of 60gsm hand sheets were produced for each level, and 0% was introduced as a control. The properties such as thickness, Canadian Standard Freeness Test, Cobb test, tensile index, folding endurance, and tear index were evaluated according to the TAPPI Standard. From the result, an 8% dosage of this commercial cationic starch exhibited the best performance in mechanical tests without compromising the drainage of water significantly.
Keywords: Cationic starch; Recycled Pulp; Paper packaging